Profil Pasar Daging Ayam Potong di Pasar Gunung Tua Padang Lawas Utara - Kartika, Aulia Arum Chandra; Sari, Ricca; Rianita, Resti; Jati, Putri Zulia (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the shape of the broiler market in the Gunung Tua market, North Padang Lawas Utara, Province Sumatra Utara. The objects observed in this study were the broiler traders and the transactions that occurred in the Gunung Tua market. This study used a survey method with census techniques and direct observation. Where the results showed that 97% consisted of retailers and 3% of wholesalers/agents. The average education is high school with a range of 50%. The average Marker Share of wholesalers to wholesalers is 13.33-32.87%. The market for broiler chicken in the Gunung Tua market, North Padang Lawas Utara Sumatra Utara is in the form of an oligopoly. From the results of this study it can be concluded that the form of the market for broiler chicken in the Gunung Tau market, North Padang Lawas Utara, Sumatra Utara is oligopoly.